Prosthetic Rehabilitation of a Patient with Limited Mouth Opening following Partial Maxillectomy and Lateral Rhinotomy for Sinonasal Adenocarcinoma: A Clinical Report - Shah, Shabir A; Naqash, Talib Amin; Zargar, Nazia Majeed (Journal of Orofacial Research, 2013)
Adenocarcinomas of various types comprise 10 to 20% of all primary malignant neoplasms of the nasal cavity and paranasal sinuses. They are thought to originate from seromucous glands of the nasal cavity and paranasal sinuses as well as the surface epithelium. Long-term prognosis is poor and patients usually die due to local spread with no metastasis. This clinical report describes a method for prosthetic rehabilitation of a patient with sinonasal adenocarcinoma of maxilla following partial maxillectomy and lateral rhinotomy.